ChemInform Abstract: A Strained Disilane‐Promoted Carboxylation of Organic Halides with CO2 under Transition‐Metal‐Free Conditions. Issue 12 (March 2016) - Mita, Tsuyoshi; Suga, Kenta; Sato, Kaori; Sato, Yoshihiro
Abstract: The carboxylation of a wide range of organic iodides (40 examples) proceeds at an ambient CO2 atmosphere at room temperature within 2 hours.